OPTIMIZATION OF PLANTING GEOMETRY AND HAULM KILLING DAYS FOR INCREASING PRODUCTION OF SEED SIZE TUBERS IN POTATO - jagannath, murlidhar sadawarti (Potato Journal, 2022)
A field experiment was conducted for two consecutive years 2018-19 and 2019-20 with high bulking early potato cultivar Kufri Khyati at Central Potato Research Institute, RS, Gwalior in split plot design with six planting geometries as main plots viz S1-60√20 cm (Control), S2-66√15 cm, S3-66√20 cm, S4-75 √15 cm, S5-75√20 cm and S6-paired row and three haulm killing dates as sub plots viz 70, 80 and 90 days after planting. For growth parameters, only planting geometry 66√15 cm recorded significantly higher plant height (52.6 cm) over other planting geometries.75√15 cm (52.6) and 75√20 cm (50.2) planting geometry recorded non significant but higher compound leaves/plant over other plant geometries. Days to haulm killing did not influence the growth parameters viz, stem, compound leaves and plant height. Significant increasing trend was recorded for number and weight of seed size and total tubers with increasing planting geometry over wider plant geometry 75√20 cm (285 thousand/ha, 17.41 t/ha seed size tuber and 671 thousand/ha, 34.52 t/ha for total tuber) and highest was recorded in paired row planting (487 thousand/ha, 29.52 t/ha seed size tuber and 1040 thousand/ha, 45.93 t/ha total tuber). Paired row planting with 70 days of haulm killing recorded significantly highest seed size (516 thousand/ha) and total tuber number (1092 thousand/ha). By number 60√20 cm planting geometry at 80 days of haulm killing (51.15% and 0.957) and by weight paired row planting at 70 days of haulm killing (73.15% and 0.367) recorded significantly highest seed size tubers percent and best seed: non seed ratio over other factor combinations. Planting geometry 66√15 cm at 80 days haulm killing (11.3) and 75√15 cm at 90 days of haulm killing (11.7) recorded significantly highest seed multiplication rate by number and weight respectively. Paired row planting with 70 days haulm killing gave highest seed size tuber yield, per cent seed size tuber and best seed: non seed ratio but planting geometry with 66√20 cm and haulm killing at 70 days found to be economically viable option for the farmers with higher B:C ratio (1.75) for seed production of variety Kufri Khyati.